Why are suicide rates rising in young men but falling in the elderly?—a time-series analysis of trends in England and Wales 1950–1998 - Gunnell, David; Middleton, Nicos; Whitley, Elise; Dorling, Daniel; Frankel, Stephen (My University, 2003)
Suicide rates doubled in males aged o45 in England and Wales between 1950 and 1998, in contrast rates declined in older males and females of all ages. Explanations for these divergent trends are largely speculative, but social changes are likely to have played an important role. We undertook a time-series analysis using routinely available age- and sexspecific suicide, social, economic and health data, focussing on the two age groups in which trends have diverged most—25–34 and 60+ year olds. Between 1950 and 1998 there were unfavourable trends in many of the risk factors for suicide: rises in divorce, unemployment and substance misuse and declines in births and marriage. Whilst economic prosperity has increased, so too has income inequality. Trends in suicide risk factors were generally similar in both age– sex groups, although the rises in divorce and markers of substance misuse were most marked in 25–34 year olds and young males experienced the lowest rise in antidepressant prescribing. Statistical modelling indicates that no single factor can be identified as underlying recent trends. The factors most consistently associated with the rises in young male suicide are increases in divorce, declines in marriage and increases in income inequality. These changes have had little effect on suicide in young females. This may be because the drugs commonly used in overdose—their favoured method of suicide—have become less toxic or because they are less affected by the factors underlying the rise in male suicide. In older people declines in suicide were associated with increases in gross domestic product, the size of the female workforce, marriage and the prescribing of antidepressants. Recent population trends in suicide appear to be associated with by a range of social and health related factors. It is possible that some of the patterns observed are due to declining levels of social integration, but such effects do not appear to have adversely influenced patterns in older generations.
Keywords: Suicide; Temporal trends; Time series; England and Wales; Socioeconomic factors; Gender